COMPANIES AND UNIVERSITIES: RANKING OF COOPERATION PERFORMANCE - Dmitry A. Endovitsky; Sergey N. Komendenko (Высшее образование в России)
Purpose. The purpose of this paper is to present a methodology for monitoring the cooperation between the business community and the system of higher education on the regional level and spotting active participants of such cooperation. The received data are to be used for developing the support policy of the effective partnership models by state government and entrepreneurs associations. Methodology/approach. The monitoring was carried out with respect to the Voronezh region companies and universities in May-June 2015 (the data was collected for the year 2014). The research method involves surveying regional universities and building composite ratings of companies based on their involvement in higher education and considering the range of cooperation forms and their value. The research data analysis included pre-verification and allowed for measurement error. The final ranking used integral binary criteria. Findings. The research results provide statistics with regard to the abundance of specified forms of cooperation between universities and companies. It also points out groups of companies exercising significant influence over the region's system of education. The ranking of companies is used by the Voronezh region government and the Chamber of Commerce and Industry and was used as a basis for similar research in other regions as well as a prototype for a methodology of monitoring the cooperation between companies and institutions of secondary professional education. Originality/value. For the first time, an assessment of the scale of and factual abundance of specified forms of cooperation between the Russian business community and the system of higher education has been performed. The results obtained can be of interest to those researching functioning of the Triple Helix model (partnership between government, companies and education) in Russia as well as to authors of higher educational institution rankings.